2001
DOI: 10.1046/j.1365-2249.2001.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CXCR1 and CXCR2 expression on human neutrophils upon activation of whole blood byS. aureusis mediated by TNF-α

Abstract: SUMMARYIt was suggested that bacterial products can inhibit the expression of leucocyte chemokine receptors during sepsis and affect leucocyte functions in septic syndrome. Superantigens and toxins produced by Staphylococcus aureus are capable of activating leucocytes via binding to MHC-II antigens on monocytes and T-cell receptor molecules on T lymphocytes. It was recently shown that staphylococcal enterotoxins directly down-regulate the expression of CC chemokine receptors on monocytes through binding to MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…The chemokine receptors CXCR1 and CXCR2 are central for many PMN functions. 29 Although some reports have shown that in vitro treatment with cytokines and/or bacterial products could downregulate CXCR1 and CXCR2 expression on human neutrophils, 23,30 studies with patients with sepsis, confirming our data, showed that expression of CXCR1, the high-affinity receptor for IL-8, were not altered in sepsis. 31,32 Most neutrophil chemoattractants recognize membrane GPCR on the leukocytes and, as a result of receptor activation by the chemoattractant, a complex sequence of signaling events are triggered, inducing profound alterations in cytoskeleton dynamics and activating signaling pathway, allowing neutrophils to develop motile, adhesive, phagocytic, and antimicrobial responses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The chemokine receptors CXCR1 and CXCR2 are central for many PMN functions. 29 Although some reports have shown that in vitro treatment with cytokines and/or bacterial products could downregulate CXCR1 and CXCR2 expression on human neutrophils, 23,30 studies with patients with sepsis, confirming our data, showed that expression of CXCR1, the high-affinity receptor for IL-8, were not altered in sepsis. 31,32 Most neutrophil chemoattractants recognize membrane GPCR on the leukocytes and, as a result of receptor activation by the chemoattractant, a complex sequence of signaling events are triggered, inducing profound alterations in cytoskeleton dynamics and activating signaling pathway, allowing neutrophils to develop motile, adhesive, phagocytic, and antimicrobial responses.…”
Section: Discussionsupporting
confidence: 88%
“…23 Fluorescence microscopy for F-actin, phosphotyrosine or GRK The contents of F-actin, GRK2, GRK5, and tyrosine-phosphorylated residues were determined in neutrophils stimulated with IL-8, LTB 4 , or zymosan by fluorescence microscopy. After treatment, neutrophil slides were prepared by cytospin centrifuge, and F-actin was stained with TRITC-labeled phalloidin (Sigma, St Louis, MO).…”
Section: Cxcr1 Expressionmentioning
confidence: 99%
“…6 A total of 10 L each final PCR product was fractionated in 1.5% agarose gel in the presence of ethidium bromide. Quantitation of fluorescence of cellular product bands was performed with Scion Image Software (Frederick, MD).…”
Section: Reverse Transcriptase-polymerase Chain Reaction Analysis Of mentioning
confidence: 99%
“…5,6 Approval was obtained from the institutional review board at the Institute of Hematology and Blood Transfusion, Minsk, Belarus, for these studies. Informed volunteer consent was obtained according to the Declaration of Helsinki.…”
Section: Study Design Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation